EphrinB2/EphA4-mediated activation of endothelial cells increases monocyte adhesion. Issue 2 (December 2015) - Poitz, David M.; Ende, Georg; Stütz, Beryl; Augstein, Antje; Friedrichs, Jens; Brunssen, Coy; Werner, Carsten; Strasser, Ruth H.; Jellinghaus, Stefanie
Highlights: Short-time activation of endothelial cells by ephrinB2 enhances monocyte adhesion. EphrinB2 mediates monocyte adhesion via the EphA4 receptor. EphrinB2 is involved in TNF-α mediated monocyte adhesion. EphrinB2 is activated by inflammatory stimuli in endothelial cells and macrophages. EphrinB2 is expressed in atherosclerotic macrophages. Abstract: The membrane anchored ligand ephrinB2 belongs to the broad Eph/ephrin system and is able to activate different Eph receptors. The Eph receptors belong to the huge group of receptor-tyrosine kinases. Eph receptors as well as their corresponding ephrin ligands are cell-membrane attached proteins. Therefore, direct cell–cell contact is essentially for interaction. It is known that ephrinB2 plays a pivotal role in developmental and in tumour angiogenesis. Previous studies point to a crucial role of the EphA4-receptor in the process of monocyte adhesion. Since ephrinB2 is known as an interaction partner of EphA4, the aim of the present study was to investigate a possible interplay of EphA4-receptor with ephrinB2 during monocyte adhesion to the endothelium. As verified by bulk adhesion assays and atomic-force microscopy based single-cell force spectroscopy, temporary stimulation of endothelial cells from different sources with the soluble ligand ephrinB2 increased monocyte adhesion to endothelial cells. The proadhesive effect of ephrinB2 was independent of an active transcription, but is mediated via the Rho signaling pathway with subsequent modulation of the actin cytoskeleton. Furthermore, ephrinB2 mediated its impact on monocyte adhesion via the receptor EphA4 as shown by siRNA-mediated silencing. Interestingly, ephrinB2 was induced by TNF-α treatment. Silencing of ephrinB2 led to a lowering of the TNF-α mediated monocyte adhesion to endothelial cells. Furthermore, immunohistochemical staining of human atherosclerotic plaque revealed expression of ephrinB2 in macrophages. The results of the present study point to a crucial role of ephrinB2 induced EphA4 forward signaling in the context of monocyte adhesion to endothelial cells. This transcription-independent effect is mediated by Rho signaling induced actin-filament polymerization.